The economic emergency: an insufficient solution (1997)
There are many reasons for the Colombian recession that began in 1995, but the disagreement between fiscal and monetary authorities is an outstanding one. Monetary measures against inflation promoted high interest rates, made real investment more risky, rocketed the exchange rate, attracted foreign capital and elevated public debt costs.Emergency measures announced early in the year were insufficient because the problem comes from old and needs long range measures. Balanced budget is a valid target, but along the economic cycle and not in each fiscal year. Reduction of public expenses or public debt must be applied in periods of growth and not when taxes go down because a recession has begun. Monetary policy must allow for anti-cyclical measures and can do it effectively by controlling the volume. of credit accessible to the Government, or to finance private construction of public works, or to those that will buy the facilities and services that get privatized.